Efektivitas Learning from Home Selama Pandemi Covid-19 di SMP Negeri 2 Sindang Kabupaten Indramayu Jawa Barat - Cecep Mujamil (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
The purpose of this study is to analyze the effectiveness of the implementation of the learning from home (BDR) process during the Covid-19 pandemic at SMP Negeri 2 Sindang Indramayu Regency. This study used a combination method (mixed methods). The data collection technique used is questionnaires that are given to students once a month. The subject of this study is a student of SMP Negeri 2 Sindang Indramayu Regency. Based on the results of the study, in general, the implementation of learning from home (BDR) in students of SMP Negeri 2 Sindang Indramayu Regency runs quite effectively with a percentage of 60-79%. The implementation of learning from home has less good effectiveness in the difficulty of understanding subjects, materials, and evaluation processes. Recommended in learning from home (BDR), teachers are required to be able to design learning activities from planning to evaluation in a simpler, creative and effective way.